Republic of Uzbekistan : Fiscal Transparency Evaluation. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Fiscal Transparency Evaluation report highlights that Uzbekistan is embarking on a comprehensive reform program to strengthen public financial management and fiscal transparency. Wide-ranging reforms to improve the coverage, reliability, quality, and accessibility of fiscal reports are being developed and implemented, and some good progress already made. This assessment of fiscal transparency practices has been undertaken to support the government's efforts to increase transparency by identifying priority areas for reform. An evaluation of practices against the IMF's Fiscal Transparency Code (the Code) finds that tangible gains have been made over 2017 and 2018. In several areas where Uzbekistan's practices do not currently meet the basic standard required under the Code, quick progress can be made. The report also provides a more detailed evaluation of Uzbekistan's fiscal transparency practices and recommended reform priorities. Strengthening legislative oversight of the state budget with a view to reducing the extent to which in-year changes can be made to aggregate expenditures without prior parliamentary approval.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet